Idiom Arab Dilihat dari Makna Tekstual dan Kontekstual - Muhammad Isya (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This paper aims to explain Arabic idioms in terms oftextual and contextual aspects. This library researchused the descriptive method, which is to describe thetext objectively. The stages in this research are datacollection, data analysis, interpretation of data, and aconclusion that will be formulated from the focus ofresearch. This research found that textual analysis inArabic idioms can sometimes be linked to contextualmeanings and some are not. That shows that thecontextual meaning itself cannot completely ignore thetextual, lexical or literal meaning. In fact, theconnection between the meanings will make it easierto memorize or understand the contextual meaning ofa particular idiom.The function of Arab